1987
DOI: 10.1021/jm00394a011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiinflammatory activities of 3-(3,5-di-tert-butyl-4-hydroxybenzylidene)pyrrolidin-2-ones

Abstract: A series of 3-(3,5-di-tert-butyl-4-hydroxybenzylidene)pyrrolidin-2-ones was synthesized and evaluated as candidate antiinflammatory/analgesic agents as well as dual inhibitors of prostaglandin and leukotriene synthesis. Some compounds that showed dual inhibitory activity were found to possess equipotent antiinflammatory activities to indomethacin, with reduced ulcerogenic effects. One of the compounds, N-methoxy-3-(3,5-di-tert-butyl-4-hydroxybenzylidene)pyrrolidin-2-o ne, was found to have a wider safety margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…23 Therefore, compounds with antioxidant properties would be expected to be potential inhibitors of 5-LO. [24][25][26][27][28] Furthermore, oxygen free radicals, which are inflammatory mediators of considerable importance, may be inactivated by such Compounds. 29 » 30 Although there have been attempts to develop new therapeutically effective derivatives of anthralin, such as triacetoxyanthracene 31 2 and butantrone 12 (3) for which initial reports were promising, later reports have indicated that these compounds were less effective and more irritating than anthralin itself.…”
mentioning
confidence: 99%
“…23 Therefore, compounds with antioxidant properties would be expected to be potential inhibitors of 5-LO. [24][25][26][27][28] Furthermore, oxygen free radicals, which are inflammatory mediators of considerable importance, may be inactivated by such Compounds. 29 » 30 Although there have been attempts to develop new therapeutically effective derivatives of anthralin, such as triacetoxyanthracene 31 2 and butantrone 12 (3) for which initial reports were promising, later reports have indicated that these compounds were less effective and more irritating than anthralin itself.…”
mentioning
confidence: 99%
“…A solution of 2,4-dibromobutyroyl chloride 23 (2; 1.32 g; 4.95 mmol) in dry DCM (30 mL) was added at À20…”
Section: -Benzyloxy-3-bromopyrrolidin-2-one (5a)mentioning
confidence: 99%
“…After 6 h, the mice were sacrificed; the stomach was removed and opened along the greater curvature, washed with distilled water and cleaned gently by dipping in saline. The mucosa damage for each stomach was examined using a stereoscopic microscope and compared with the reference drug indomethacin according to the reported procedure [36].…”
Section: Ulcerogenic Activitymentioning
confidence: 99%